On some properties of the spaces of almost continuous functions - Ryszard Jerzy Pawlak (International Journal of Mathematics and Mathematical Sciences)
In this paper we prove that, in the space 𝒜 of almost continuous functions (with the metric of uniform convergence), the set of functions of the first class of Baire is superporous at each point of this space